Coating slurry based on porous MOFs materials and its application, composite diaphragm, lithium-ion battery
By using composite coating slurry of porous MOFs material and alumina ceramics in the lithium-ion battery separator, the existing separator has solved the problems of low liquid absorption and poor liquid retention performance, achieving higher liquid absorption and liquid retention performance, and improving the battery's circulation performance and energy density.
Patent Information
- Application Number
- CN202411797225.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-08
AI Technical Summary
The existing lithium-ion battery separators have problems such as small liquid absorption and poor liquid retention performance, which leads to poor circulation performance of the battery cell.
A coating slurry based on porous MOFs material is used, which contains MOFs material, alumina ceramics, binders, dispersants and organic solvents, as the coating material of the separator to improve the liquid absorption and liquid retention properties of the separator.
This technology effectively improves the liquid absorbing volume and liquid retention performance of the diaphragm, reduces the internal resistance of the battery, and improves the circulation performance and energy density of lithium-ion batteries.
Smart Images

Figure CN119775893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a coating slurry based on porous MOFs materials and application thereof, a composite diaphragm and a lithium ion battery. Background Art
[0002] With the rapid popularization of new energy vehicles, the market has put forward higher requirements for lithium-ion batteries. Researchers have invested more R&D efforts in improving battery performance, focusing more on improving energy density, safety and cycle performance. Lithium-ion battery components mainly include positive electrode, negative electrode, diaphragm and electrolyte as well as a series of auxiliary materials. Among them, the diaphragm is one of the four main materials of lithium-ion batteries. During the battery charging and discharging process, it mainly allows lithium ions to pass through but does not conduct electrons, thus acting as a barrier to the positive and negative electrodes.
[0003] At present, the diaphragms widely used in the industry are mainly based on polyolefins PE or PP. In order to improve safety performance, Al2O3 or boehmite is usually used as a ceramic coating on the surface of the base film, which can improve the thermal shrinkage safety performance of the diaphragm. With the improvement of people's requirements for energy density and performance, the development of diaphragms needs to have lightweight characteristics, while also being able to store more electrolyte and maintain the original mechanical strength, which is beneficial to the battery's cycle performance and energy density. However, the ceramic coating material itself has a small specific surface area, which is not conducive to liquid absorption; its densely stacked thin coating often has poor liquid retention performance for the battery cell, which is not conducive to the long-term cycle performance of the battery cell.
[0004] CN116435709A discloses a composite coating diaphragm for ion batteries and a preparation method thereof, wherein the composite coating diaphragm is composed of a base film and a single-sided or double-sided coating applied to the surface of the base film, and the coating is formed by a composite of a porous material and a ceramic material. The porous material is selected from at least one of natural zeolite, synthetic zeolite, UIO-66, ZIF-70, ZIF-67, ZIF-8, MIL-100, Fe-BTC, Cu-BTC, and MOF-177. The ceramic material is selected from at least one of high-purity alumina, boehmite, boron nitride, silicon nitride, and silicon carbide; the preparation process is to mix and grind the porous material with the ceramic material, mix with an adhesive and a solvent to form a coating slurry, and apply it on the surface of the base film to form. The composite coating diaphragm can improve the wettability, thermal stability, flame retardancy, and electrochemical properties of the diaphragm, but it still has the defects of poor liquid retention effect and low liquid absorption. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that the battery separator in the prior art has low liquid absorption and poor liquid retention performance, resulting in poor cycle performance of the battery core.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a coating slurry based on porous MOFs material, wherein the coating slurry contains MOFs material, alumina ceramic, a binder, a dispersant and an organic solvent;
[0007] Wherein, based on the total weight of the coating slurry, the content of the MOFs material is 12-50wt%, the content of the alumina ceramic is 12-60wt%, the content of the binder is 2.3-15wt%, the content of the dispersant is 0.1-1wt%, and the content of the organic solvent is 25-61wt%;
[0008] The specific surface area of the MOFs material is 520-1300m 2 / g, pore volume is 0.2-0.7cm 3 / g;
[0009] The average particle diameter of the alumina ceramic is 4-8 μm.
[0010] The second aspect of the present invention provides the use of the coating slurry based on the porous MOFs material described in the first aspect in a diaphragm.
[0011] A third aspect of the present invention provides a composite diaphragm, the composite diaphragm comprising a base membrane and a diaphragm coating applied to the upper and lower surfaces of the base membrane;
[0012] The diaphragm coating is formed from the coating slurry described in the first aspect.
[0013] A fourth aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and a composite separator;
[0014] The composite diaphragm is the composite diaphragm described in the third aspect.
[0015] Through the above technical solution, the present invention has at least the following advantages:
[0016] (1) The coating slurry based on the porous MOFs material provided by the present invention is applied to the diaphragm coating. The diaphragm coating is applied to the soft-pack lithium-ion battery and can absorb more electrolyte. It can effectively solve the problems of low liquid absorption and low liquid retention in the existing coating diaphragm, thereby achieving the purpose of reducing internal resistance and improving cycle performance.
[0017] (2) The composite diaphragm provided by the present invention can maintain its thermal shrinkage performance and good thickness uniformity when applied to lithium-ion batteries; and compared with the existing coated diaphragms, at the same coating thickness, the coating weight of the diaphragm of the present invention is lighter, which is beneficial to improving the energy density of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1is a schematic diagram of the composite diaphragm of the present invention;
[0019] Figure 2 is a schematic diagram of a lithium-ion battery of the present invention;
[0020] Figure 3 It is a cycle performance curve diagram of the lithium ion battery prepared in Application Example 1 of the present invention and Comparative Application Example 1. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] In the present invention, MOFs refers to Metal-Organic Frameworks, which is a crystalline porous material with a periodic network structure formed by self-assembly of inorganic metal centers (such as metal ions or metal clusters) and organic ligands.
[0023] In the present invention, the PE separator refers to a polyethylene separator.
[0024] As mentioned above, the first aspect of the present invention provides a coating slurry based on porous MOFs material, wherein the coating slurry contains MOFs material, alumina ceramic, a binder, a dispersant and an organic solvent;
[0025] Wherein, based on the total weight of the coating slurry, the content of the MOFs material is 12-50wt%, the content of the alumina ceramic is 12-60wt%, the content of the binder is 2.3-15wt%, the content of the dispersant is 0.1-1wt%, and the content of the organic solvent is 25-61wt%;
[0026] The specific surface area of the MOFs material is 520-1300m 2 / g, pore volume is 0.2-0.7cm 3 / g;
[0027] The average particle diameter of the alumina ceramic is 4-8 μm.
[0028] Preferably, the particle size D of the MOFs material is 50 The inventors have found that in this preferred case, the technical solution provided by the present invention can obtain a composite diaphragm with better performance in the later stage of the cycle.
[0029] It should be noted that in the present invention, the particle size D 50 It refers to the particle size corresponding to when the cumulative particle size distribution of MOFs material measured by a laser particle size analyzer reaches 50%, that is, particles with a particle size smaller than this particle size account for 50%.
[0030] Preferably, the MOFs material is MOF-Zn and / or MOF-Co. In this preferred case, the technical solution provided by the present invention can obtain a composite diaphragm with better liquid retention capacity and circulation performance.
[0031] Preferably, based on the total weight of the coating slurry, the content of the MOFs material is 14-30wt%, the content of the alumina ceramic is 17-22wt%, the content of the binder is 2.8-8wt%, the content of the dispersant is 0.15-0.3wt%, and the content of the organic solvent is 40-61wt%. In this preferred case, the technical solution provided by the present invention can obtain a composite diaphragm with more uniform coating and better liquid absorption and liquid retention performance.
[0032] According to a preferred embodiment, the MOFs material is prepared by a method comprising the following steps:
[0033] (S1) contacting and mixing the metal salt and water I to obtain a mixed solution I;
[0034] (S2) contacting and mixing the mixed solution I and the nitrogen-containing organic ligand II to obtain the MOFs material.
[0035] Preferably, the molar ratio of the metal salt to the nitrogen-containing organic ligand is 1:2-50.
[0036] Preferably, in the mixed solution I, the concentration of the metal salt is 1.3-1.9 wt %.
[0037] Preferably, the conditions of the contact mixing I and the contact mixing I each independently include: a temperature of 15-45° C. and a time of 5-120 min.
[0038] According to another preferred embodiment, the MOFs material is prepared by a method comprising the following steps:
[0039] (T1) contacting and mixing the nitrogen-containing organic ligand and the alcohol solvent ⅠⅠⅠ to obtain a mixed solution Ⅰ;
[0040] (T2) contacting and mixing the mixed solution I with a metal salt to obtain the MOFs material.
[0041] According to a preferred embodiment, the alcohol solvent Ⅲ is methanol and / or ethanol, preferably methanol.
[0042] Preferably, the molar ratio of the metal salt to the nitrogen-containing organic ligand is 1:30-40.
[0043] Preferably, in the mixed solution I, the concentration of the nitrogen-containing organic ligand is 19-25 wt %.
[0044] Preferably, the conditions of the contact mixing-1 and the contact mixing-2 independently include: a temperature of 20-30° C. and a time of 30-120 min.
[0045] According to a most preferred embodiment, the MOFs material is prepared by a method comprising the following steps:
[0046] (1) subjecting the metal salt and the alcohol solvent I to a first contact mixing to obtain a mixed solution I; and
[0047] The nitrogen-containing organic ligand and the alcohol solvent ⅠⅠ are contacted and mixed for the second time to obtain a mixed solution ⅠⅠ;
[0048] (2) The mixed solution I and the mixed solution Ⅱ are subjected to a third contact mixing to obtain the MOFs material.
[0049] Preferably, the alcohol solvent I and the alcohol solvent II are each independently methanol and / or ethanol, preferably methanol.
[0050] Preferably, the molar ratio of the metal salt to the nitrogen-containing organic ligand is 1:25-40.
[0051] Preferably, in the mixed solution I, the concentration of the metal salt is 1.4-1.9 wt %.
[0052] Preferably, in the mixed solution Ⅱ, the concentration of the nitrogen-containing organic ligand is 17-26 wt%, preferably 19-26 wt%.
[0053] Preferably, the nitrogen-containing organic ligand is an imidazole compound, preferably 2-methylimidazole; and the metal salt is a zinc salt and / or a cobalt salt.
[0054] Preferably, the zinc salt is selected from zinc nitrate and / or zinc chloride.
[0055] Preferably, the cobalt salt is cobalt nitrate.
[0056] Preferably, the conditions for the first contact mixing include: a temperature of 15-45° C. and a time of 10-70 min.
[0057] Preferably, the second contact mixing conditions include: temperature of 15-45° C. and time of 5-15 min.
[0058] Preferably, the conditions for the third contact mixing include: temperature of 15-45° C. and time of 110-130 min.
[0059] Preferably, the binder is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose and polyacrylic acid, and the weight average molecular weight of the binder is 2,000-1.5 million.
[0060] Preferably, the binder is polyvinylidene fluoride.
[0061] Preferably, the dispersant is polyethylene glycol and / or sodium polyacrylate, and the weight average molecular weight of the dispersant is 20,000-100,000.
[0062] Preferably, the dispersant is polyethylene glycol.
[0063] Preferably, the organic solvent is selected from at least one of N-methylpyrrolidone, dimethylformamide and acetone, preferably N-methylpyrrolidone.
[0064] As mentioned above, the second aspect of the present invention provides the use of the coating slurry based on the porous MOFs material described in the first aspect in a diaphragm.
[0065] As mentioned above, the third aspect of the present invention provides a composite diaphragm, which includes a base membrane and a diaphragm coating coated on the upper and lower surfaces of the base membrane;
[0066] The diaphragm coating is formed from the coating slurry described in the first aspect.
[0067] Preferably, the surface density of the coating is 1.2-1.6 g / m 2 .
[0068] Preferably, the base film is a PE diaphragm.
[0069] Preferably, the coating method is selected from at least one of micro-gravure roller coating, slot extrusion coating and slide extrusion coating.
[0070] The present invention has no special requirements for the method for making the composite membrane, and those skilled in the art can make it using conventional methods. The specific method for making the composite membrane is exemplarily provided in the following text of the present invention, which should not be construed as a limitation of the present invention by those skilled in the art.
[0071] The present invention is exemplarily Figure 1 A schematic diagram of the composite membrane is provided, wherein a represents the membrane coating and b represents the PE base film.
[0072] As mentioned above, the fourth aspect of the present invention provides a lithium ion battery, which comprises a positive electrode sheet, a negative electrode sheet and a composite separator;
[0073] The composite diaphragm is the composite diaphragm described in the third aspect.
[0074] The present invention has no special requirements for the manufacturing method of the positive electrode sheet and the negative electrode sheet. Those skilled in the art can use conventional methods to manufacture them. The specific manufacturing method of the positive electrode sheet and the negative electrode sheet is exemplified in the following text of the present invention, which should not be understood by those skilled in the art as a limitation of the present invention.
[0075] The present invention is exemplarily Figure 2 A schematic diagram of the above-mentioned lithium-ion battery is provided.
[0076] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the compounds and reagents used are all commercially available, and the reagents are all analytically pure.
[0077] 2-Methylimidazole, purchased from Aladdin, CAS No. 1739-84-0, purity 98%.
[0078] The following preparation examples are used to illustrate the preparation method of the MOFs material of the present invention.
[0079] Preparation Example 1: Preparation of MOFs Materials
[0080] (1) subjecting the metal salt and alcohol solvent I (methanol) to a first contact mixing (temperature of 25° C., time of 10 min) to obtain a mixed solution I; and
[0081] The nitrogen-containing organic ligand (2-methylimidazole) and the alcohol solvent ⅠⅠ (methanol) are subjected to a second contact mixing (temperature of 25°C, time of 10 minutes) to obtain a mixed solution ⅠⅠ;
[0082] (2) The mixed solution I and the mixed solution Ⅱ were subjected to a third contact mixing (temperature of 30° C., time of 120 min) to obtain MOFs material.
[0083] The raw materials and their ratios in this preparation example and the characteristic parameters of the MOFs materials are shown in Table 1.
[0084] The methods for preparing MOFs materials used in the remaining preparation examples of the present invention are the same, except that the raw materials and their ratios are different, and MOFs materials with different characteristic parameters are obtained respectively. The raw material ratios and process parameters of the MOFs materials are listed in Table 1, and the unlisted parts are the same as those in Preparation Example 1.
[0085] Table 1 (the amount of metal salt used is 0.8g)
[0086]
[0087] Note: The molar ratio 1 refers to the molar ratio of the metal salt and the nitrogen-containing organic ligand.
[0088] The following examples are used to illustrate the preparation method of the composite diaphragm of the present invention.
[0089] Example 1
[0090] The binder (polyvinylidene fluoride) and the organic solvent (N-methylpyrrolidone) are stirred and dissolved to form a glue solution, and the MOFs material and alumina ceramic powder with an average particle diameter of 6 μm are added. At the same time, a dispersant (polyethylene glycol) is added and stirred to make each component evenly dispersed to form a coating slurry;
[0091] The coating slurry was evenly coated on the upper and lower surfaces of the porous base membrane (PE diaphragm), and the coating surface density was controlled to be 1.4 g / m 2 , and a composite diaphragm is obtained after drying.
[0092] The specific materials of this example are shown in Table 2.
[0093] The remaining examples were prepared using the same preparation method as Example 1, except that the materials were different, as shown in Table 2.
[0094] Table 2 (each 1wt% represents 1g)
[0095] Example 1 Example 2 Example 3 MOFs Materials type Z1 Z2 Z3 Dosage / wt% 22 30 14 Alumina ceramics Dosage / wt% 17.6 18 21.4 Binder Dosage / wt% 4.7 5.6 3.5 Dispersants Dosage / wt% 0.15 0.3 0.2 Organic solvents Dosage / wt% 55.55 46.1 60.9
[0096] Example 4
[0097] A composite membrane is obtained by a method similar to that of Example 1, except that the MOFs material Z1 in Example 1 is replaced by Z4 of equal mass and the rest are the same.
[0098] Example 5
[0099] A composite membrane is obtained by a method similar to that of Example 1, except that the MOFs material Z1 in Example 1 is replaced by Z5 of equal mass and the rest are the same.
[0100] Comparative Example 1
[0101] A composite membrane is obtained by a method similar to that of Example 1, except that the MOFs material Z1 in Example 1 is replaced by DZ1 of equal mass and the rest are the same.
[0102] Comparative Example 2
[0103] A composite membrane was obtained by a method similar to that of Example 1, except that the MOFs material Z1 in Example 1 was replaced by DZ2 of equal mass and the rest was the same.
[0104] The following application examples are used to illustrate the lithium ion battery of the present invention.
[0105] Application Example 1
[0106] (1) Using lithium iron phosphate LFP or ternary material, and conductive agent (carbon nanotube CNT), binder (polyvinylidene fluoride PVDF) uniformly dispersed in N-methylpyrrolidone NMP, after stirring and dispersing to make positive electrode slurry, it is coated on aluminum foil, dried, and rolled to make positive electrode sheet;
[0107] (2) artificial graphite is uniformly dispersed in deionized water with a conductive agent (conductive carbon black SP), a binder (styrene-butadiene rubber SBR), and a dispersant (carboxymethyl cellulose CMC), and the negative electrode slurry is prepared by stirring and dispersing, and the negative electrode slurry is coated on a copper foil, dried, and rolled to prepare a negative electrode sheet;
[0108] (3) The positive electrode sheet, the negative electrode sheet and the composite separator prepared in Example 1 are stacked into an electrode group in the form of a laminate, which is sealed intact with an aluminum-plastic film. The electrolyte is injected and allowed to stand to allow the electrode group to fully absorb the electrolyte. A small current is then charged to activate the battery. Finally, the battery is vacuum-sealed to complete the production of a finished battery cell. The battery capacity is designed to be 38 Ah, thereby obtaining a lithium-ion battery.
[0109] Application Example 2-5
[0110] A lithium ion battery was obtained by a method similar to that of Application Example 1, except that the composite diaphragm prepared in Example 1 was replaced by the composite diaphragms prepared in Example 2, Example 3, Example 4, and Example 5, respectively.
[0111] Comparative Application Example 1-2
[0112] A lithium ion battery was obtained by a method similar to that of Application Example 1, except that the composite diaphragm prepared in Example 1 was replaced by the composite diaphragms prepared in Comparative Example 1 and Comparative Example 2, respectively.
[0113] Test Example 1
[0114] The lithium-ion battery obtained in the application example was subjected to a liquid retention capacity test and a cycle performance test. The liquid retention capacity test results are shown in Table 3.
[0115] Among them, liquid absorption rate = (mass after liquid absorption m2-mass before liquid absorption m1) / mass before liquid absorption m1;
[0116] Filling coefficient = amount of electrolyte injected into the cell / cell capacity;
[0117] Liquid loss coefficient = a certain amount of electrolyte lost during vacuum packaging during the production of soft-pack batteries (referred to as "liquid loss") / battery capacity;
[0118] Liquid retention coefficient = amount of electrolyte retained inside the battery after production / battery capacity.
[0119] Table 3
[0120]
[0121] The present invention is exemplarily Figure 3 The cycle performance curves of the lithium ion batteries prepared in Application Example 1 and Comparative Application Example 1 are provided; wherein, Cycle 1 represents the lithium ion battery prepared in Application Example 1, and Cycle 2 represents the lithium ion battery prepared in Comparative Application Example 1. Figure 1 It can be seen that the coating slurry based on the porous MOFs material provided by the present invention is applied to the diaphragm coating, and the prepared lithium-ion battery has better cycle performance. This is attributed to the fact that the diaphragm coating can store more electrolyte. As the battery charge and discharge cycle proceeds, the electrolyte is continuously consumed, and the electrolyte stored in the diaphragm is replenished in time, which is beneficial to the deintercalation and extraction of lithium ions, reduces the internal resistance and thus improves the cycle performance.
[0122] It can be seen from the above results that the liquid absorption rate of the PE diaphragm is 100%, while the composite diaphragm provided by the present invention has a higher liquid absorption rate when applied to lithium-ion batteries. The amount of liquid loss during vacuum sealing in the battery cell manufacturing process is reduced, and the liquid retention coefficient is higher. In addition, since the electrode group of the battery cell absorbs more electrolyte, there is less free electrolyte, so the hardness and appearance of the battery cell are better.
[0123] This shows that the coating slurry based on the porous MOFs material provided by the present invention is applied to the diaphragm coating. The diaphragm coating applied to the soft-pack lithium-ion battery can absorb more electrolyte, which can effectively solve the problems of low liquid absorption and low liquid retention in the existing coating diaphragm, thereby achieving the purpose of reducing internal resistance and improving cycle performance.
[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A coating slurry based on porous MOFs material, characterized in that: The coating slurry contains MOFs material, alumina ceramics, a binder, a dispersant and an organic solvent; Wherein, based on the total weight of the coating slurry, the content of the MOFs material is 12-50wt%, the content of the alumina ceramic is 12-60wt%, the content of the binder is 2.3-15wt%, the content of the dispersant is 0.1-1wt%, and the content of the organic solvent is 25-61wt%; The specific surface area of the MOFs material is 520-1300m 2 / g, pore volume is 0.2-0.7cm 3 / g; The average particle diameter of the alumina ceramic is 4-8 μm.
2. The coating slurry according to claim 1, wherein: The particle size D of the MOFs material 50 0.1-2μm; And / or, the MOFs material is MOF-Zn and / or MOF-Co.
3. The coating slurry according to claim 1 or 2, wherein: Based on the total weight of the coating slurry, the content of the MOFs material is 14-30wt%, the content of the alumina ceramic is 17-22wt%, the content of the binder is 2.8-8wt%, the content of the dispersant is 0.15-0.3wt%, and the content of the organic solvent is 40-61wt%.
4. The coating slurry according to any one of claims 1 to 3, wherein: The MOFs material is prepared by a method comprising the following steps: (1) subjecting the metal salt and the alcohol solvent I to a first contact mixing to obtain a mixed solution I; as well as The nitrogen-containing organic ligand and the alcohol solvent ⅠⅠ are contacted and mixed for the second time to obtain a mixed solution ⅠⅠ; (2) The mixed solution I and the mixed solution Ⅱ are subjected to a third contact mixing to obtain the MOFs material.
5. The coating slurry according to claim 4, wherein: The molar ratio of the metal salt to the nitrogen-containing organic ligand is 1:25-40; And / or, the nitrogen-containing organic ligand is an imidazole compound; and the metal salt is a zinc salt and / or a cobalt salt.
6. The coating slurry according to any one of claims 1 to 5, wherein: The binder is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose and polyacrylic acid, and the weight average molecular weight of the binder is 2,000-1.5 million; And / or, the dispersant is polyethylene glycol and / or sodium polyacrylate, and the weight average molecular weight of the dispersant is 20,000-100,000; And / or, the organic solvent is selected from at least one of N-methylpyrrolidone, dimethylformamide and acetone.
7. Use of the coating slurry based on porous MOFs material according to any one of claims 1 to 6 in a diaphragm.
8. A composite diaphragm, characterized in that: The composite diaphragm comprises a base membrane and a diaphragm coating applied on the upper and lower surfaces of the base membrane; The diaphragm coating is formed from the coating slurry according to any one of claims 1 to 6.
9. The composite diaphragm according to claim 8, wherein: The surface density of the coating is 1.2-1.6 g / m 2 ; And / or, the base film is a PE diaphragm.
10. A lithium ion battery, characterized in that: The lithium-ion battery contains a positive electrode sheet, a negative electrode sheet and a composite diaphragm; The composite diaphragm is the composite diaphragm according to claim 8 or 9.
Citation Information
Cited By
Asymmetrically structured co-coated separator, method of making the same, and secondary battery
CN122512120A